2022
DOI: 10.1002/mus.27760
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of creatine kinase and creatinine levels in Duchenne muscular dystrophy

Abstract: Introduction/Aims: Management of Duchenne muscular dystrophy (DMD) has entered an era featuring novel treatments. Trackable noninvasive biomarkers could improve disease progression monitoring and drug effect detection. Our aim in this study was to measure changes in selected noninvasive biomarkers and assess their relationship to age and motor function.Methods: We retrospectively studied 555 patients with DMD who had at least 12 months of treatment of glucocorticoids and were not enrolled in trials of potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Moreover, although individual biomarker values are challenging to directly apply clinically, a recent study has demonstrated that trends of selected non-invasive biomarkers over time (as CK, serum creatinine, urine creatinine) may complement functional measures in the assessment of individuals with DMD [57].…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Moreover, although individual biomarker values are challenging to directly apply clinically, a recent study has demonstrated that trends of selected non-invasive biomarkers over time (as CK, serum creatinine, urine creatinine) may complement functional measures in the assessment of individuals with DMD [57].…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Over the decade long trial, there were no adverse effects associated with chronic ASA treatment and disease progression was significantly slowed as measured by clinical blood biomarker of muscle necrosis, CK, the urinary creatinine:creatine ratio and the distal (finger) muscle strength test. Notably, plasma/serum CK levels are prone to fluctuation in DMD and can markedly drop due to muscle loss in advanced disease [ 27 ]. However, compellingly, in one patient with slower, atypical onset (but confirmed) DMD [ 28 ], serum CK levels were attenuated by increasing ASA dosage; 73 mg/kg/day ASA saw CK levels of 1000–2000 U/L (normal range 20–200 U/L) whereas, when ASA treatment was periodically discontinued for 6 months, CK levels were elevated to ~20,000 U/L [ 26 ].…”
Section: Asa: Biological Activity and Pharmacologymentioning
confidence: 99%
“…3,4 The large-scale studies have been conducted in countries other than Japan in this regard. [5][6][7] The aim of the present study was to examine the longitudinal data of Japanese DMD patients collectively and assess individual patients with pathogenic variants eligible for exon-skipping therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the need to elucidate the natural history of DMD has been greatly emphasized, and natural history data are being collected 3,4 . The large‐scale studies have been conducted in countries other than Japan in this regard 5–7 …”
Section: Introductionmentioning
confidence: 99%